Pengaruh Penggunaan E-Learning Madrasah Terhadap Hasil Belajar Akidah Akhlak Siswa - Sinta Salasatunisa; Nurhidayat Nurhidayat; Gilang Maulana Jamaludin (Indonesian Journal of Islamic Education, 2023)
The purpose of this study was to find out: 1) The use of madrasah e-learning media in class VIII students in the Akidah Akhlak subject at MTsN 2 Sumedang, 2) The learning outcomes of class VIII students in the Akidah Akhlak subject, 3) The effect of using madrasah e-learning on learning outcomes of class VIII students in the Akidah Akhlak subject at MTsN 2 Sumedang. This research method is quantitative ex post facto with the research object of class VIII students at MTsN 2 Sumedang. The measurement scale in this study uses a Likert scale. The results of the study show that the use of madrasah e-learning at MTsN 2 Sumedang can be implemented properly. This is evidenced by the questionnaire score obtained and the respondent's level of achievement of 75.64% so that it can be categorized as good. The learning outcomes of Grade VIII students in the Aqidah Akhlak subject at MTsN 2 Sumedang are in the very good category. With an average value of 80.7 achieved. The results of the hypothesis are based on a significance value of (0.749) > (0.05) and an R Square of 0.002 which indicates that the level of influence of variable X on variable Y is 2% very small.